ANALISIS STRATEGI PEMBELAJARAN KURIKULUM MERDEKA PADA SISWA KELAS 4 DI SDN BASIRIH 4 BANJARMASIN - M. Dhika Chilman Azizy; Hidya Maulida; Sa’adah Erliani (Berajah Journal, 2025)
This research aims to analyze the learning strategies used by teachers in implementing the Merdeka Curriculum for class IV students at SDN Basirih 4. The focus of the research is directed at planning and implementing learning in accordance with the principles of the Merdeka Curriculum, namely learner-centred learning, differentiation and strengthening the Pancasila student profile. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. The research subjects were class IV teachers and students at SDN Basirih 4. The research results showed that the teachers had implemented project-based, collaborative and contextual learning strategies in accordance with the characteristics of the Merdeka Curriculum. At the planning stage, teachers develop teaching modules and diagnostic assessments to map student learning needs. At the implementation stage, differentiation strategies are used in learning activities, both from the content, process and product aspects. Meanwhile, at the evaluation stage, teachers use formative and summative assessments which emphasize achieving competency and strengthening student character. However, there are several obstacles, such as limited learning resources, time management, and quite a variety of student abilities. Overall, the learning strategies implemented by class IV teachers at SDN Basirih 4 are in line with the principles of the Independent Curriculum, but still require strengthening in terms of the use of digital learning media and increasing teacher competence in developing learning differentiation.